Scientific and Philosophical explanations: learning metacognitive skills - Martén Saborío, Sergio (2023)
The article utilizes an epistemological framework (Khalifa, 2017) which facilitates loose definitions of the concepts of knowledge and explanation to contrast their scientific version with the philosophical one —specifically scientific knowledge with specifically philosophical knowledge—. Through this contrast, the particularities of explanation in each of these disciplines is revealed, as well as the kinds of questions that they aim to answer —open or closed— and the resources they use to do so —empirical or conceptual—. Based on the former, the main argument of this paper concludes that there are strong reasons to assume that the teaching of philosophy in itself promotes the teaching of cognitive and metacognitive skills that are not covered by the teaching of science, and that they are as relevant as the ones that it does cover. Furthermore, it is shown that there is a clear lack of quantitative studies to back this conclusion, and that it is important to fill this academic void moving forward.